Strategies for people with intellectual disability to engage in social policy-related self-advocacy in South Africa - Goldberg, Nicole (Department of Psychiatry and Mental Health, 2024)
Aim: This study investigated strategies for people with intellectual disability to self-advocate for inclusion of their priorities in social policy processes in South Africa. Method: Self-advocacy strategies were identified through a scoping literature review, a review of self-advocacy toolkits and semistructured interviews with people with intellectual disability and other stakeholders working at nongovernmental and disabled people's organisations. The data were triangulated to identify common strategies which can best support self-advocacy for people with intellectual disability. In addition, these findings informed the development of a local self-advocacy toolkit which was reviewed by a group of young adults with intellectual disability. The toolkit provides an evidence-based compilation of strategies for self advocacy that can be used by self -advocates with intellectual disability and their supporters in the local context. Results: Data triangulation identified three core strategies for selfadvocacy, specifically, (1) strategies for in-person self-representation in public spaces, (2) written communication strategies, and (3) engagement through social and other forms of media. These were incorporated into the self-advocacy toolkit. The experiential review of the toolkit yielded positive feedback from participants. As part of the experiential review, participants related to the idea of social media advocacy by choosing to produce a video as their self-advocacy activity, aimed at sharing their perspectives on the way they experience society and social policy. Discussion: Inclusion of people with intellectual disability in civic and political life is crucial and will only be achieved if self-advocates are accepted into the policy-making arena. Strategies are available for people with intellectual disability to challenge the status quo of society in which prejudice and stigma continue to impact on their inclusion in social discourse. By using these self-advocacy strategies, people with intellectual disability can have a say in policy decisions which impact on their lives. Conclusion: Self-advocacy to enhance policy participation can promote the inclusion of the voices of people with intellectual disability to influence public social policy decisions. Adopting strategies which enable the inclusion of the voices of people with intellectual disability in civic activities holds potential for diversifying perspectives brought to public participation in policy development and implementation, which is currently primarily the domain of citizens without disability.